Fatigue analysis of tympanic membrane after ossiculoplasty. (3rd July 2017) - Zhou, Lei; Feng, Miaolin; Huang, Xinsheng; Duan, Maoli
Abstract: Conclusion: A tentative conclusion was made that the finite element method can be used to investigate the fatigue life of the tympanic membrane after ossiculoplasty; the main reason of the extrusion of the tympanic membrane may not be blamed to the fatigue mechanism under normal sound pressure. Objective: This study was to investigate the extrusion of the prosthesis from the tympanic membrane at post-ossiculoplasty by finite element method. Methods: A finite element model of the human middle ear has been constructed and used as the model of the constructed middle ear at post-ossiculoplasty. Then the fatigue life of the tympanic membrane was calculated under different sound pressure level using this model. Results: The tympanic membrane would not be extruded under normal sound pressure level. The sound pressure level which caused the tympanic membrane to crack in less than 3 years was higher than 145.17 dB (362.5 Pa).